Implementasi Pendidikan Dalam Pengabdian Masyarakat Melalui Pemanfaatan Media Animasi Islami di MTs Terpadu Berkah Palangka Raya - Zaitun Qamariah; Hesty Widiastuty; Alya Audria; Rini Listiya Ningrum; Siti Rahmawati (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This research explores the synergy between lecturers, students and alumni of the Arabic and English Education Technology Study Program (TBI) at IAIN Palangka Raya in carrying out collaborative community service activities. The main focus of this research is the application of Islamic animation media as a means of strengthening verb language skills in students at the Berkah Palangka Raya Integrated Tsanawiyah Madrasah. The research method used is qualitative. The aim of this research is to improve the understanding and use of verbs in Arabic among MTs Terpadu Berkah Palangka Raya students. The research results show that through this collaborative approach, lecturers, students and alumni can create Islamic animated media that is interesting and relevant to the students' context. The use of Islamic animation media is effective in strengthening students' understanding of verb skills, as well as increasing their learning motivation. This research contributes to a practical understanding of how synergy between lecturers, students and alumni can improve collaborative community service in the field of education.